Ejector performance prediction at critical and subcritical operational modes - Li, F.; Tian, Q.; Wu, Changzhi; Wang, Xiangyu; Lee, J. (Elsevier, 2017)
Traditional ejector models are focusing on the ejector performance predictions at critical mode under design conditions. In reality, ejector systems cannot be operated under these conditions perfectly. Thus, the study of ejector performance at subcritical mode under off-design conditions is important. In this paper, novel models for ejector performance predictions at critical point and breakdown point are developed based on constant-pressure mixing and constant-pressure disturbing assumptions. Then, the two models are integrated as the model to predict ejector performance at critical and subcritical operational modes. In order to determine the ejector component efficiencies in the models, a novel concept, the effect of the change (EOC) of efficiency, is introduced to identify the efficiencies which affect ejector performance significantly. Then, the identified efficiencies are determined by sparsity-enhanced optimization method. The predicted results obtained by our model are much more accurate than those obtained by existing methods.